Étude des représentations sociales de la culture occitane chez les élèves de Calandretas - Grégoire Andreo-Raynaud (Lengas)
This paper aims to propose some reflections about the transmission of an endangered culture in a scholar context. Those reflections are based on an exploratory survey conduct with school students between 9 and 11 years old from Calandretas primary schools. Calandretas are associative schools teaching Occitan language through immersion. The goal is to understand social representations of Occitan culture which circulate in the students population, and their connections with cultural transmission mechanisms. In the first part, I am doing a small summary about the concepts of culture, language and heritage, and about the necessity to link these notions to analyse the sociolinguistic dynamic of Occitan language. The second part is dedicated to the description of the investigation protocol and the discussion of the results